Research collaboration for a knowledge-based economy: towards a conceptual framework - Mavis Serwah Benneh Mensah; Francis Enu-Kwesi (Triple Helix, 2018)
A knowledge-based economy thrives on constructed advantages generated through well-planned recursive interactions among key actors in the economy. Using a desk review, this paper advances theoretical and conceptual arguments in support of research collaboration as a critical and viable medium for the conduct of research and innovation geared towards economic growth and development. We propose a conceptual framework to guide future research on the determinants and the dynamics of research collaboration as well as the use of collaborative research output in innovation. The framework, which can be modelled, is recommended for descriptive and explanatory research aimed at obtaining first-hand information for policy interventions that seek to advance the knowledge-based economy, through research collaboration.
Keywords: 330; Collaboration; Economy; Innovation; Knowledge; Research